The impact of parental involvement and education on academic achievement in elementary school - Miranda Avnet; David Makara; Karen H Larwin; Matthew Erickson (International Journal of Evaluation and Research in Education (IJERE), 2019)
The academic achievement of students in schools is subject to a variety of factors, many of which are beyond the control of the student. Factors such as parental involvement, parental level of education, and disability all influence the academic achievement and learning of students. The study analyzed nation-wide survey data on students in elementary school and investigates the relationship between student achievement and multiple variables. The variables were parental involvement, and the existence of Autism Spectrum Disorder (ASD) or other disability. Results indicated that students, both ASD and typically developing, have lower parent involvement if they are successful in school.